2022
DOI: 10.3389/fnhum.2022.906188
|View full text |Cite
|
Sign up to set email alerts
|

Beauty and Uncertainty as Transformative Factors: A Free Energy Principle Account of Aesthetic Diagnosis and Intervention in Gestalt Psychotherapy

Abstract: Drawing from field theory, Gestalt therapy conceives psychological suffering and psychotherapy as two intentional field phenomena, where unprocessed and chaotic experiences seek the opportunity to emerge and be assimilated through the contact between the patient and the therapist (i.e., the intentionality of contacting). This therapeutic approach is based on the therapist’s aesthetic experience of his/her embodied presence in the flow of the healing process because (1) the perception of beauty can provide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 293 publications
1
14
0
Order By: Relevance
“…In line with the learning theories of aesthetics, we previously suggested that aesthetic appreciation (and, as we discuss below, the expectancy of the reward associated with it, i.e. aesthetic attitude ) can switch our emotional state from anxiety to curiosity (see the section Beauty Makes Us Curious and Less Anxious in [58]) and can function as a ‘valve’ [12] that redirects attentional resources from self-related exploitation (i.e. goal directed behaviour based on previously acquired action policies) to contemplative learning-oriented exploration [59].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In line with the learning theories of aesthetics, we previously suggested that aesthetic appreciation (and, as we discuss below, the expectancy of the reward associated with it, i.e. aesthetic attitude ) can switch our emotional state from anxiety to curiosity (see the section Beauty Makes Us Curious and Less Anxious in [58]) and can function as a ‘valve’ [12] that redirects attentional resources from self-related exploitation (i.e. goal directed behaviour based on previously acquired action policies) to contemplative learning-oriented exploration [59].…”
Section: Introductionmentioning
confidence: 78%
“…Protracted maladaptive exteroception may cause adjustments in metacognitive (second order) beliefs resulting in pathological anxiety, in which neutral sensory and social stimuli are evaluated as threating and uncertainty is avoided. In short, anxious agents have learned that surprise cannot be reduced by learning and therefore try to avoid it [44,124]. We have already demonstrated that music listening can reduce performances in heart beat detection [59], which on the contrary is increased during anxious states [126][127][128].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, certain life events or situations may also trigger them, such as the loss of a loved one or a major life transition (Sarasso et al 2022; Gaggioli and Others 2016; W. R.…”
Section: Ellenberger 1968mentioning
confidence: 99%